Impact of integrating guidelines into an antimicrobial stewardship smartphone application on outpatient antibiotic prescribing: a segmented interrupted time series analysis - Sadeq, Ahmed A.; Alhaj Ali, Laila Z.; Shamseddine, Jinan M.; Conway, Barbara R.; Bond, Stuart E.; Ali, Rizwan; Lattyak, William J.; Babiker, Zahir Osman Eltahir; Aldeyab, Mamoon A. (Frontiers in Digital Health, 2025)
IntroductionAntimicrobial stewardship (AMS) smartphone applications (apps) have been adopted to promote better antimicrobial prescribing practices. We aimed to evaluate the impact of incorporating an app on AMS metrics and adherence to a local antimicrobial guideline in an outpatient setting.MethodsA quasi-experimental, segmented interrupted time series design was used, involving three study phases (pre-intervention: 1st January 2020 to 31st December 2021; implementation: 1st January 2022 to 31st December 2022, and post-intervention: 1st January 2023 to 30th June 2024) in a hospital outpatient setting. The effect of introducing an AMS app incorporating local antimicrobial guidelines on AMS outcomes was measured.ResultsA total of 24,424 patients were identified. As per the most simple model, the amounts of the following antibiotics, expressed as defined daily dose (DDD) per 100 patient visits, increased significantly during the post-intervention phase: azithromycin (co-efficient 0.297, p = 0.007), co-amoxiclav (co-efficient 2.608, p = 0.042), and nitrofurantoin (co-efficient 0.908, p = 0.003). The trend in fosfomycin use decreased significantly in the post-intervention phase (co-efficient −0.23., p < 0.001). Guideline adherence increased significantly after implementing the AMS app (trend change co-efficient 0.011, p < 0.001). These changes in antibiotic prescribing represent improved guideline adherence, and are aligned with WHO AWaRe categorisation recommendations.ConclusionThe app improved the utilization of antibiotic prescribing by increasing adherence to local antimicrobial guidelines, affirming its utility in augmenting AMS in outpatient settings.